Foley's Threshold View of Belief and The Safety Condition on Knowledge. (24th July 2018) - Shaffer, Michael J.
Abstract: This paper introduces a new argument against Richard Foley's threshold view of belief. Foley's view is based on the Lockean Thesis (LT) and the Rational Threshold Thesis (RTT). The former thesis is the claim that it is epistemically rational to believe a proposition if and only if it is epistemically rational to have a degree of confidence in that proposition sufficient for belief. The latter thesis is the claim that it is epistemically rational to believe a proposition if and only if it is epistemically rational to have a degree of confidence in that proposition that meets or exceeds a specified threshold. The argument introduced here shows that the views derived from the joint endorsement of the LT and the RTT violate the safety condition on knowledge in way that threatens the LT and/or the RTT.